Efficacy of ultrasound guided dry needling as an adjunct to conventional physical therapy for patients with jumper’s knee: A randomized controlled trial - Sharif, Faiza; Ahmad, Ashfaq; Gilani, Syed Amir; Bacha, Raham; Hanif, Asif; Arif, Muhammad Asim (Frontiers in Surgery, 2022)
Background: Jumper’s knee is a degenerative condition among athletes, and it has been treated with several conventional interventions. Ultrasound-guided dry needling (USG-DN) is a relatively new technique to explore the clinical outcomes in patients of tendinopathy. Methods: This parallel group, single-blinded randomized controlled trial was carried out involving ninety-four athletes with clinically diagnosed jumper’s knee, divided into intervention group (USG-DN+CPT, n=47) and a control group (CPT, n=47). Participants received 4-weeks programme; the intervention group received ultrasound guided patellar tendon dry needling in conjunction with conventional interventions. The control group received only conventional physical therapy. The visual analogue scale (VAS), Victorian institute of sports assessment-Patellar tendinopathy (VISA-P) questionnaire, Lysholm scale, Knee injury and osteoarthritis outcome score (KOOS) and ultrasonographic features of patellar tendinopathy were evaluated at baseline of 1 week, 2 weeks and 4 weeks. The data were analyzed through SPSS-26. Results: There were significant differences(p<0.05) between the two groups, after first week of intervention in the USG-DN+CPT group (1.2±0.15 points on VAS) and even more so after the second intervention (3±0.01 points on VAS). After 4 weeks pain intensity differed from baseline by (5.2±0.68 points on VAS). Statistically significant differences (p<0.05) in Lysholm and VISA-P were also found between the intervention group and the control group. After the fourth week, a significant increase in Lysholm and VISA-P within USG-DN+CPT group (83.40±5.78) & (88.70±8.59) respectively were observed. KOOS scale also showed highly significant differences. After 4 weeks, a statistically significant increase (p<0.05) in KOOS scale was observed between both groups. Conclusion: The results of the current study suggest, ultrasound guided dry needling of patellar tendon in combination with conventional intervention reduced pain, improved function, and showed a tendency to decreased tendon thickness in patients with patellar tendinopathy.